Plesiomonas: A Review on Food Safety, Fish-Borne Diseases, and Tilapia - Alejandro De Jesús Cortés-Sánchez; Luis Daniel Espinosa-Chaurand; Mayra Díaz-Ramirez; Erika Torres-Ochoa (The Scientific World Journal)
Fish and fish products are considered a fundamental part of the human diet due to their high nutritional value. Food-borne diseases are considered a major public health challenge worldwide due to their incidence, associated mortality, and negative economic repercussions. Food safety is the guarantee that foods will not cause harm to the health of those who consume them, and it is a fundamental property of food quality. Food safety can be at risk of being lost at any stage of the food chain if the food is contaminated by pathogenic microorganisms. Many diverse bacteria are present in the environment and as part of the microbiota of food that can be transmitted to humans during the handling and consumption of food. Plesiomonas shigelloides has been mainly associated with outbreaks of gastrointestinal diseases due to the consumption of fish. This bacterium inhabits the environment and aquatic animals and is associated with the microbiota of fish such as tilapia, a fish of importance in fishing, aquaculture, commercialization, and consumption worldwide. The purpose of this document is to provide, through a bibliographic review of databases (Scopus, Web of Science, and Google Scholar, among others), a general informative perspective on food-borne diseases and, in particular, the consumption of fish and tilapia. Diseases derived from contamination by Plesiomonas shigelloides are included, and control and prevention actions and sanitary regulations for fishery products established in several countries around the world are discussed to promote the safety of foods of aquatic origin intended for human consumption and to protect public health.